Nowe metody leczenia autoimmunologicznych zapalnych schorzeń narządu wzroku - Kubicka-Trząska, Agnieszka; Undas, Anetta (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The authors review the current literature, regarding the efficacy and safety of new methods of therapy for ocular inflammatory autoimmune diseases: scleritis, pemphigoid and uveitis. Immunomodulation therapy is increasingly being used in various ocular inflammatory diseases, to avoid the effects of long-term steroid and immunosuppressive therapy and to induce remission in chronic disease. This therapy seems to be effective specially in treating resistant disease with relative safety. New approaches to therapy of intraocular inflammatory diseases will emphasize less immunosuppressive drugs and modification of the immune system with anti-MHC II, anti-adhesion molecules, anticytokines monoclonal antibodies, therapy with cytokines antagonists, intravenous immunoglobulin therapy, INF alpha therapy, antigen specific tolerancing therapy and gene therapy. Advances in the understanding of pathogenesis and in diagnostic techniques in various ocular inflammatory entities, will serve as a driving force for these new methods of treatment.